Influence of Different Textures on Machining Performance of a Milling Tool - Jianfeng Pan; Kai Feng; Lihua He; Kai Zhuang; Jing Ni; Junjie Lv (Advances in Materials Science and Engineering)
Milling plays a significant role in the machining of aluminum alloy parts. However, in the milling process, the material easily adheres to the tip of the milling tool due to the high ductility and thermal deformation of the aluminum alloy; the machining efficiency and quality are hard to further improve. Hence, in order to promote the machining performances, three textures (linear, wavy, and micropitted) are prepared, respectively, on rake face of milling tools using the laser processing system. Then, milling load, top-burrs, and surface quality are chosen to discuss the machining performance of textured milling tools. In particular, the top-burrs are investigated by relative area ratio of top-burrs (RARB) which is calculated from the micrograph after binarization. The obtained results evidently show that the wavy textured milling tool reduces the milling load by an amount of 10.7% compared to the nontextured milling tool. This is due to the smaller contact area that reduces the internal friction of the tool-chip contact area and thus reduces the load. And surface roughness improves by an amount of 23.8% because the wavy texture has the largest proportion of the unit area, and it can effectively improve the storage capacity of debris. Therefore, the wavy texture proposed in this research is of great reference value for the optimization of the machining performance of the milling tool.